The allosteric enhancer PD81,723 increases chimaeric A(1)/A(2A) adenosine receptor coupling with G(s) - Bhattacharya, Samita (Portland Press Ltd., 2006)
PD81,723 {(2-amino-4,5-dimethyl-3-thienyl)-[3-(trifluromethyl)-phenyl]methanone} is a selective allosteric enhancer of the G(i)-coupled A(1) AR (adenosine receptor) that is without effect on G(s)-coupled A(2A) ARs. PD81,723 elicits a decrease in the dissociation kinetics of A(1) AR agonist radioligands and an increase in functional agonist potency. In the present study, we sought to determine whether enhancer sensitivity is dependent on coupling domains or G-protein specificity of the A(1) AR. Using six chimaeric A(1)/A(2A) ARs, we show that the allosteric effect of PD81,723 is maintained in a chimaera in which the predominant G-protein-coupling domain of the A(1) receptor, the 3ICL (third intracellular loop), is replaced with A(2A) sequence. These chimaeric receptors are dually coupled with G(s) and G(i), and PD81,723 increases the potency of N(6)-cyclopentyladenosine to augment cAMP accumulation with or without pretreatment of cells with pertussis toxin. Thus PD81,723 has similar functional effects on chimaeric receptors with A(1) transmembrane sequences that couple with G(i) or G(s). This is the first demonstration that an allosteric regulator can function in the context of a switch in G-protein-coupling specificity. There is no enhancement by PD81,723 of G(i)-coupled A(2A) chimaeric receptors with A(1) sequence replacing A(2A) sequence in the 3ICL. The results suggest that the recognition site for PD81,723 is on the A(1) receptor and that the enhancer acts to directly stabilize the receptor to a conformational state capable of coupling with G(i) or G(s).